Health and marital status of older Chinese couples and implications for intergenerational co-residence. Issue 9 (6th September 2021) - Kumar, Sneha; Williams, Lindy
Abstract: Older individuals who are in poor health or who lack spousal support are in many ways vulnerable in contemporary China. Declines in family size, combined with improvements in life expectancy and the out-migration of young adults from rural areas, have reduced the pool of potential care-givers for a growing number of older individuals. At the same time, state support for elderly people remains inadequate, further emphasising families' role in care provision. This paper uses couple-level panel data from the 2012, 2014 and 2016 China Family Panel Studies to examine whether older couples with health-care or other needs receive help in the form of intergenerational co-residence. Multinomial logistic regressions are used to examine factors associated with the intergenerational solidarity framework from the older parents' perspective that could motivate co-residence. Results show that when mothers report activity limitations or poor word recall at baseline, or when at least one parent has activity limitations in both waves, the probability of co-residence in both waves increases. Further, when both parents have depression at baseline, or when a parent loses a spouse, the probability of transitioning to co-residence increases. Findings suggest that adult children in present-day China do respond to parental needs by living together. Nevertheless, going forward, the state will likely have to play a greater role in old-age care provision.